Evaluation of Learning Media Quality for Islamic Religious Education at Kadiri University, Indonesia - Risni, Titin Widya; Mochammad Danara Indra Pradigta; Pamadya Vitasmoro; Shahzadi Hina (Journal of Islamic Education Research, 2025)
This study aims to evaluate the quality of learning media used in the Islamic Religious Education course at Kadiri University, Indonesia. The evaluation focuses on the learning media and supporting facilities within the classroom, including projectors, screens, audio systems, and physical conditions such as seating, room temperature, and elevator accessibility. A qualitative descriptive approach based on Miles and Huberman's model was employed, with data collected through direct observation and in-depth interviews involving five students from the Faculty of Health Sciences who attended the course during the odd semester. The findings reveal that the quality of learning media and facilities generally supports an effective and comfortable learning environment. Well-functioning projectors, audio systems, and comfortable seating are key factors in facilitating the learning process. The availability of an elevator also enhances mobility for students and lecturers between floors, contributing to smoother lecture activities. However, several issues were noted, including deteriorating chair conditions and inconsistent air conditioning performance in some instances. This study highlights the importance of routine maintenance to ensure the quality of classroom facilities and optimize the learning experience. Furthermore, it opens avenues for future research on the relationship between facility quality, student learning outcomes, and the integration of advanced technology in learning media for Islamic Religious Education.